Secondary analysis of APPLE study suggests atorvastatin may reduce atherosclerosis progression in pubertal lupus patients with higher C reactive protein. Issue 3 (22nd February 2013) - Ardoin, Stacy P; Schanberg, Laura Eve; Sandborg, Christy I; Barnhart, Huiman X; Evans, Greg W; Yow, Eric; Mieszkalski, Kelly L; Ilowite, Norman T; Eberhard, Anne; Imundo, Lisa F; Kimura, Yuki; Levy, Deborah; et al.
Abstract : Objective: Participants in the Atherosclerosis Prevention in Paediatric Lupus Erythematosus (APPLE) trial were randomised to placebo or atorvastatin for 36 months. The primary endpoint, reduced carotid intima medial thickness (CIMT) progression, was not met but atorvastatin-treated participants showed a trend of slower CIMT progression. Post-hoc analyses were performed to assess subgroup benefit from atorvastatin therapy. Methods: Subgroups were prespecified and defined by age (> or ≤15.5 years), systemic lupus erythematosus (SLE) duration (> or ≤24 months), pubertal status (Tanner score ≥4 as post-pubertal or <4 as pre-pubertal), low density lipoprotein cholesterol (LDL) (≥ or <110 mg/dl) and high-sensitivity C reactive protein (hsCRP) (≥ or <1.5 mg/l). A combined subgroup (post-pubertal and hsCRP≥1.5 mg/l) was compared to all others. Longitudinal linear mixed-effects models were developed using 12 CIMT and other secondary APPLE outcomes (lipids, hsCRP, disease activity and damage, and quality of life). Three way interaction effects were assessed for models. Results: Significant interaction effects with trends of less CIMT progression in atorvastatin-treated participants were observed in pubertal (3 CIMT segments), high hsCRP (2 CIMT segments), and the combined high hsCRP and pubertal group (5 CIMT segments). No significant treatment effect trends were observed across subgroups defined by age, SLE duration, LDL for CIMT or other outcome measures. Conclusions: Pubertal status and higher hsCRP were linked to lower CIMT progression in atorvastatin-treated subjects, with most consistent decreases in CIMT progression in the combined pubertal and high hsCRP group. While secondary analyses must be interpreted cautiously, results suggest further research is needed to determine whether pubertal lupus patients with high CRP benefit from statin therapy. ClinicalTrials.gov identifier: NCT00065806.